HUBUNGAN INTERTEKSTUAL PUISI “MUNIR MENENGGAK RACUN” KARYA YOSEPH YAPI TAUM DAN PUISI “SAJAK UNTUK SEBUAH NAMA (CAK MUNIR)” KARYA PRAMASTA SAID - Angela Klaudia Danu; Petrus Sii; Priska Filomena Iku; Claudia Oktafiani Samador (Jurnal Pendidikan dan Kebudayaan Missio, 2022)
This study aims to understand the depth of meaning of poetry which has an intertextual relationship with other poetry works. The researcher used Abrams's structural approach to analyze the similarities and differences between the poems that were analyzed. The method used in this study is a qualitative descriptive method. Sources of data in this study are the poem "Munir Menenggak Racun" by Yoseph Yapi Taum in 2011 and the poem "Sajak Untuk Sebuah Nama (Cak Munir)" by Pramasta Said in 2014. The data are in the form of words, phrases, lines, stanzas, and rhythm related to the intertextual study of poetry. The data collection technique used was reading and note-taking techniques related to the intertextual study of the two poems. Data analysis in this study is a content analysis by comparing and equating the intertextuality of the two poetry texts. The results of this study reveal the similarity of the hypogram based on the analysis of the physical and mental structure of the poem. The hypograms of the two data sources in this study were found in the characterization elements, namely Munir, the figurative language hypogram, the imagery hypogram, the plot hypogram, the theme and mandate hypogram, and the cacophony variety hypogram. The two poems are ballad that reveal socio-political issues related to the death of Munir, a human rights activist. The final conclusion of the general hypogram of the two texts is found in the poem "Munir Menenggak Racun" by Yoseph Y.T. Meanwhile, the poem "Sajak Untuk Sebuah Nama (Cak Munir)" by Pramasta Said is the result of the transformation of the general hypogram text which has the same background in the creation process and describes the ethical social, and political problems that occur in Indonesia.